2006
DOI: 10.1007/s11661-006-0044-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability in bulk cryomilled ultrafine-grained 5083 Al alloy

Abstract: Thermal stability in bulk ultrafine-grained (UFG) 5083 Al that was processed by gas atomization followed by cryomilling, consolidation, and extrusion, and that exhibited an average grain size of 305 nm, was investigated in the temperature range of 473 to 673 K (0.55 to 0.79 T m , where T m is the melting temperature of the material) for different annealing times. Appreciable grain growth was observed at temperatures Ͼ573 K, whereas there was limited grain growth at temperatures Ͻ573 K even after long annealing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 27 publications
5
63
1
Order By: Relevance
“…The activation energy of 5.6 kJ⋅mol −1 was determined for milled 5083 powder where there is no strain relaxation. Similar to the findings of Roy et al [34], the increase in activation energy of the Al-Mg-Er powders compared to the milled 5083 powder could be attributed to some strain relaxations taking place with increased temperature. Annealing at 150 ∘ C resulted in limited grain growth in both powders (Figures 9 and 15) and reduced microstrain from the as-milled state (i.e., 0.041% in 0.1 Er and 0.066% in 0.5 Er).…”
Section: Activation Energy For Grain Growthsupporting
confidence: 86%
See 3 more Smart Citations
“…The activation energy of 5.6 kJ⋅mol −1 was determined for milled 5083 powder where there is no strain relaxation. Similar to the findings of Roy et al [34], the increase in activation energy of the Al-Mg-Er powders compared to the milled 5083 powder could be attributed to some strain relaxations taking place with increased temperature. Annealing at 150 ∘ C resulted in limited grain growth in both powders (Figures 9 and 15) and reduced microstrain from the as-milled state (i.e., 0.041% in 0.1 Er and 0.066% in 0.5 Er).…”
Section: Activation Energy For Grain Growthsupporting
confidence: 86%
“…Another study on a bulk UFG 5083 alloy reported = 25 ± 5 kJ⋅mol −1 for the low temperature regime, while = 124 ± 5 kJ⋅mol −1 was found for higher temperatures ( > 573 K) [5,34]. Roy et al [34] suggest that the low activation energy at low temperatures is indicative of highly unstable and nonequilibrium grain boundaries. Unstable grain boundaries could require smaller driving force for rearrangement of the grains and grain boundaries, while nonequilibrium boundaries may possess greater atomic mobility due to excess dislocations [34].…”
Section: Activation Energy For Grain Growthmentioning
confidence: 95%
See 2 more Smart Citations
“…Extensive research to improve the AA5083 alloy had been conducted with emphasis on the microstructures and mechanical properties [8][9][10][11], superplasticity [12][13][14][15], ultrafine grain [16][17][18][19][20] and adding element [21][22][23][24], etc. Recently, research was carried out on the formation of the Fe-and Mn-rich intermetallics in the AA5083 type Al-Mg-Mn alloy [2].…”
Section: Introductionmentioning
confidence: 99%